RIISK FACTORS FOR IN-STENT RESTENOSIS IN PATIENTS WITH PERCUTANEOUS CORONARY INTERVENTIONS - Zimbakov, Zan; Zdravkovski, Igor; Parisko, Emilia; Jovanova, Silvana (Journal of Morphological Sciences, 2021)
Percutaneous coronary intervention (PCI) is one of the main treatments for patients with coronary heart disease (CHD), and in-stent restenosis (ISR) after PCI has gradually attracted clinical attention. Although the rates of in-stent restenosis (ISR) have been reduced dramatically with the introduction of drug-eluting stents (DESs), the ISR problem has not been completely resolved. The aim of our study was to identify the risk factors influencing the likelihood of restenosis after stent implantation. We retrospectively review 115 patients (mean age 63.4Â±0.3years) with previous PCI for acute coronary syndrome or stabile angina pectoris, hospitalized at the University clinic of cardiology in Skopje for follow-up coronary angiography. The data were obtain from coronary intervention database.  Seventy two patients were diagnosed as ISR and forty three patients had no significant ISR. Restenosis rates were higher among patients with diabetes mellitus, hiperlipidemia and smoking history and the differences between two groups were statistically significant (all p<0.05). The restenosis rates were higher in patients with BMS compared to first and second generation DESs (p<0.01). The smaller (diameter <3mm) and longer stents (>20mm) were associated with more in-stent restenosis with significant statistical difference among group ( p < 0.05). Predictors of in-stent restenosis were identified with linear regression analyses.  The diabetes, hyperlipidemia, stent features were independent risk factors for ISR (all p < 0.05). In conclusion, for patients with PCI risk factors identification and management is warranted to prevent the ISR. Keywords : percutaneous coronary intervention, in-stent restenosis, risk factor https://doi.org/10.55302/JMS2141150z